Vital real-world experience regarding Naoshuantong capsules for unselected ischemic stroke (VENUS): Rationale, design, and baseline of a prospective, multicenter, observational study - Dong, Xinglu; Feng, Luda; Li, Tingting; Song, Yuebo; Li, Lei; Wu, Shengxian; Zhang, Chi; Gao, Ying; , ; For the VENUS Investigators (Frontiers in Pharmacology, 2022)
Background：Naoshuantong capsules (NC) are commonly used for the treatment of ischemic stroke. Experimental research and small-sample clinical trials have demonstrated NC was effective in improving neurological recovery. Yet there is a substantial lack of high-quality evidence on its precision treatment population of NC and long-term safety when making real-world clinical decisions. The acquisition of prospective longitudinal data in the real-world setting is essential to fully characterize the effectiveness and safety profile of NC for patients with ischemic stroke. Methods：The Vital Real-world Experience regarding Naoshuantong Capsules for Unselected Ischemic Stroke (VENUS) registry is a prospective, multicenter, observational study aiming to register 5,000 patients. Eligible adult patients diagnosed as ischemic stroke and newly treated with NC within 30 days of symptom onset will be consecutively registered from 84 participating sites across the Chinese mainland. Baseline data will be recorded at patient registry, and all patients will be regularly followed up at 2, 4, 8, and 12 weeks after the initial patient registry, and 180 days after ischemic stroke onset. The primary outcome is the distribution of score on the modified Rankin Scale at the 12 weeks after initial patient registry. Adverse events will be recorded during the study for NC safety assessment. Results: A total of 4185 patients with ischemic stroke were enrolled, among which 37.06% patients were female. The average age of all patients was 65.22 years. The proportion of patients whose course of ischemic stroke less than 14 days accounted for 93.45%. Conclusion：The VENUS registry is designed to comprehensively document medical data regarding NC treatment for ischemic stroke in real-world settings. The findings of this study will provide valuable insights into the clinical management of patients with ischemic stroke and its subsequent outcomes of the use of NC when included in the best clinical practice.